Analisis Hubungan Kinerja Pendidik terhadap Motivasi dan Hasil SMK Kota Makassar - N, Nur Nasrah; Husain, Halimah; Salempa, Pince (Chemistry Education Review (CER), 2024)
Education at Vocational High Schools (SMK) produces graduates who are ready to enter the world of work, employment or as entrepreneurs. These conditions must be in line with the performance of educators, which requires acceleration and increased competency so that students' learning motivation is better. The aim of the research is to describe the relationship between educator performance and learning motivation and to describe the relationship between educator performance and the science and science learning outcomes of chemistry students at vocational schools in Makassar City. The research method is descriptive correlational using Rank Spearman correlation analysis. Where the independent variable is educator performance and the dependent variable is learning motivation and learning outcomes. The research population consisted of Vocational High Schools in Makassar City. Meanwhile, the sample in this study was 130 students from 5 vocational schools in Makassar City. The data collection techniques used were questionnaires and documentation. Questionnaires are used to obtain data on learning motivation and educator performance, while documentation is used to obtain data on learning outcomes, number of students, number of educators and school profile. The research results show (i) significance value or Sig. (2-tailed) is 0.008 < 0.005, meaning there is a significant relationship between performance variables and learning motivation, (ii) obtained a significance value or Sig. (2-tailed) is 0.458 so 0.458 > 0.005, meaning there is no significant relationship between performance variables and learning outcomes.